Wayang Kulit and The Growth of Islam in Java - Suhardjono, Liliek Adelina (Bina Nusantara University, 2016)
This article intended to examine the circumstance of wayang kulit during the coming of Islam in the Java island of Indonesian archipelago; how it changed and held functions within the Islamisation process of the region. The lack of written materials made this issue was somewhat unclear . In exploring these issues, this article would explain some elements surrounded Javanese wayang, specifically during the Islamisation period of Java. By showing several examples of wayang kulit characters, whether or not wayang had undertaken adaptations during this era and how far was observed. The method of this was from the data collection for that largely originated from academic books and journals from both western and Indonesian scholars, and then some visual examinations would be done upon them. The observation of each object aims to show that while to some extent wayang did undergo some alterations during this Islamisation period, however the core value of wayang performance itself was still largely Javanese, principally and aesthetically.